The Impacts of Popular Participation in the Urban Landscape: A Case Study in Lorena, SP. - Morita, Gabriela Katie Silva; Mülfarth, Roberta Consentino Kronka (Revista Nacional de Gerenciamento de Cidades, 2023)
Despite being an intrinsic factor in people’s daily lives, active mobility still presents itself as a challenge in the model of Brazilian cities due to the lack of adequate and inviting structure for walking. This case study was carried out in a city located in the countryside of the State of São Paulo, with the purpose of enabling a higher quality in walking, reinforcing walkability and the importance of more sustainable modes of transportation, fostering urban vitality and reactivating neglected areas by promoting a network articulation to develop sustainable initiatives. In this way, it seeks to highlight the importance of popular participation in the construction and requalification of urban public spaces, not only in terms of displacement, but also in the occupation of idle spaces through the use of methods and tools, such as tactical urbanism, which proposes interventions in the city in the context of the micro scale, from short-term solutions, low cost and multipliable. The study presents the challenges and the results of the project, arising from the collection and systematization of data, and from the collective construction and continuous appropriation of space by the population.